INDUSTRY COST PLANNING FEATURES WITH PRE-PRODUCTION MEDICAL EQUIPMENT AND MACHINERY - E. Shapoval; I. Nesterovа (Вестник университета, 2016)
This article explores the question of sectoral planning costs during the preparation of medical equipment and machinery. Currently, the scope of the production of medical equipment, as one of the fastest growing economy in the Russian manufacturing industries, has its own characteristics. All production plants manufacturing process is preceded by a preparatory stage. We need to study the expected cost-effectiveness of production of new products, study the effectiveness of innovation and investment.